Pulmonary Thrombosis or Embolism in a Large Cohort of Hospitalized Patients With Covid-19 - Benito, Natividad; Filella, David; Mateo, Jose; Fortuna, Ana M.; Gutierrez-Alliende, Juan E.; Hernandez, Nerea; Gimenez, Ana M.; Pomar, Virginia; Castellvi, Ivan; Corominas, Hector; Casademont, Jordi; Domingo, Pere (Frontiers in Medicine, 2020)
Objective. We sought to analyze the incidence and predictive factors of pulmonary embolism (PE) in hospitalized patients with Covid-19. Methods. We prospectively collected data from all consecutive patients with laboratory-confirmed Covid-19 admitted to the Hospital de la Santa Creu i Sant Pau, a university hospital in Barcelona, between March 9 and April 15, 2020. Patients with suspected PE, according to standardized guidelines, underwent CT pulmonary angiography (CTPA). Results. A total of 1275 patients with Covid-19 were admitted to hospital. CTPA was performed on 76 inpatients and a diagnosis of PE was made in 32 (2.6% [95CI 1.7%-3.5%]). Patients with PE were older, had lower PaO2:FiO2 ratios and higher levels of D-dimer and C-reactive protein (CRP). They more often required admission to ICU and mechanical ventilation and had longer hospital stays, although in-hospital mortality was no greater than in patients without PE. High CRP and D-dimer levels at admission (≥ 150 mg/L and ≥ 1000 ng/ml, respectively), and a peak D-dimer ≥ 6000 ng/ml during hospital stay were independent factors associated with PE. Prophylactic low molecular weight heparin did not appear to prevent PE. Increased CRP levels correlated with increased D-dimer levels and both correlated with a lower PaO2:FiO2. Conclusions. The 2.6% incidence of PE in Covid-19 hospitalized patients is clearly high. Higher doses of thromboprophylaxis may be required to prevent PE, particularly in patients at increased risk, such as those with high levels of CRP and D-dimer at admission. These findings should be validated in future studies.